Can Radiographs Predict the Use of Modular Stems in Developmental Dysplasia of the Hip?. Issue 2 (February 2016) - Peters, Christopher L.; Chrastil, Jesse; Stoddard, Gregory J.; Erickson, Jill A.; Anderson, Mike B.; Pelt, Christopher E.
Abstract: Background: Abnormal anatomy frequently results in the use of a modular stem in patients undergoing primary total hip arthroplasty (THA) for developmental dysplasia of the hip (DDH). However, because these stems are not always available in the operating room, it would be helpful if standard radiographic views could be analyzed in such a way that patients whose femoral anatomy might call for stem modularity could be anticipated before surgery. To our knowledge, no such parameters have been defined. Questions/purposes: In the senior author's practice, we used femoral neck anteversion of more than 25° as a determinant for use of a modular stem. Given this criterion, we asked if we could reliably identify plain film radiographic parameters of the femur that predict the use of modular stems. We looked at the following: (1) the neck‐shaft angle based on the anteroposterior (AP) radiograph (alpha); (2) the neck‐shaft angle from the crosstable lateral radiograph (beta); and (3) the calculated femoral anteversion angle. Methods: We reviewed preoperative radiographs from 50 of 67 patients (79 hips) who had a primary diagnosis of DDH and underwent primary THA from January 1999 to February 2007 inclusive. Hips with prior femoral‐sided surgery (n = 2) or without preoperative films (n = 19) were excluded. Furthermore, patients with bilateral hips had the second hip excluded (n = 8). Twenty‐one of 50 received a modular femoral stem based on the criterion of intraoperative neck‐shaft anteversion of greater than 25° as measured by the senior surgeon (CLP), whereas the remainder received tapered nonmodular stems. There were no differences in age, sex, height, or weight between the modular stem group and tapered stem group. Radiographs were evaluated to record the parameters listed. Results: Patients in whom modular femoral stems were used had a greater mean AP (alpha) neck‐shaft angle compared with patients who received tapered nonmodular stem (152°; 95% confidence interval [CI], 146°‐157° versus 137°; 95% CI, 134°‐141°; p < 0.001) with an optimal cutoff point for determining the use of modular stems of ≥ 142° (receiver operating characteristic [ROC] area = 73%). Hips in which modular femoral stems were chosen had a smaller mean lateral (beta) neck‐shaft angle (152°; 95% CI, 148°‐157° versus 161°; 95% CI, 158°‐164°; p = 0.003) with an optimal cutoff point of ≤ 153° (ROC area = 65%). Hips in which modular femoral stems were used had a higher femoral anteversion angle (mean 45°; 95% CI, 37°‐54° versus 21°; interquartile range, 17°‐25°; p < 0.001) with an optimal cutoff of ≥ 32° (ROC area = 80%). Conclusions: Preoperative radiographs anticipated the use of modular stems during THA for DDH in a practice where modular stems were chosen on the basis of a neck‐shaft angle of greater than 25° measured at surgery. We found that this could be predicted on preoperative radiographs based on smaller lateral neck‐shaft angles, steeper AP radiographic neck‐shaft angles, and increased femoral anteversion calculated using these angles. Prospective studies are needed to better determine if these cutoff values adequately predict the use of modular stems.